Dibujo arquitectónico: experiencias 2008-2018 - Herrera, Carlos Marcelo (2018)
The teaching-learning processes of Architectural Drawing require a thematic, operational and significant specialization, a gradual, dosed approach, guided by the teachers. The subject focuses on the understanding of drawing as a fundamental, basic and essential language for the development of architecture and for the learning of its exercise. We will review the processes developed since the beginning of the subject (2008) with the intention of constituting assessments regarding: The presence of the drawing in the 2008 Study Plan (FAUD-UNSJ). The challenges from Planning to Verifications. Teaching roles, capacities and collective and individual contributions. Introductory Practices and Academic Experiences.